(Stran)poti slovenske konkurenčne politike - Ferčič, Aleš (Podjetje in delo, 2015)
The author deals with the Slovenian competition policy after the attainment of indepen%dence. For practical reasons, the analysis is introduced with the constitutional and institutional framework. Analysis of public and private enforcement of competition law in Slovenia follows, and each subfield of competition policy and law is analysed separately. On this basis, core shortcomings of the past Slovenian competition policy and their reasons are identified and findings and theses which could be used by policy-makers when forming the future competition policy in Slovenia are offered.
Keywords: konkurenca; konkurenčna politika; konkurenčno pravo; Slovenia; Slovenija